Perancangan dan Implementasi Sistem Inventory di SMK Globe National Plus 2 Kota Batam - Hendi Sama; Jesica Jesica (National Conference for Community Service Project (NaCosPro), 2023)
The era of technology is growing rapidly and has affected every activity and facilitates human work. One example of the application of an information system is the development of an inventory system which is an activity for processing data on goods in the warehouse. SMK Globe National 2 Plus Batam is a private school owned by the Batam Bumi Cemerlang Foundation and is currently facing a problem, namely the absence of technological tools to record school assets or goods. Therefore, it is necessary to design an inventory system to make it easier to record school goods, can borrow goods and can be used in various locations. In designing a website-based inventory system, the authors use the scrum method and use the PHP programming language and MYSQL database. The results of this study are to make it easier for schools to store data on the website to make it easier to record stocks of assets or goods quickly and accurately.